An improved coordinated control strategy for boiler-turbine units supplemented by cold source flow adjustment. (August 2015) - Wang, Wei; Liu, Jizhen; Zeng, Deliang; Niu, Yuguang; Cui, Can
Abstract: CCS (coordinated control strategy) is widely used for boiler-turbine units to change their steam turbine load. However, it is almost impossible to make a breakthrough in the load change performance just through CCS on account of the boiler's large delay. In order to accelerate the unit load response speed through the CSFA (cold source flow adjustment), the static and dynamic influence model of CSFA on the turbine power output is firstly set up in this paper. Then an improved strategy which combines CCS with CSFA control is brought forward to be used for the flexible load control. Another innovation of the improved strategy is to tie the output of CSFA controller to the measurement signal of the boiler controller, through which CSFA is used to quicken the turbine load response, the coal feeder rate to ensure the steady load accuracy, and the turbine governor valve to stabilize the main steam pressure. Furthermore, the condenser pressure will be recovered to its normal value for the next load dispatch use. Finally, simulation results confirm the effectiveness of the improved strategy compared to CCS, and moreover the extra coal consumption during the control process has been proved to be very small. Highlights: Static and dynamic models of CSFA (cold source flow adjustment) are set up. An improved strategy combined CSFA and CCS (coordinated control strategy) is firstly put forward and simulated. Our strategy can significantly shorten the settle time and diminish the overshoot. Condenser pressure is resumed original for the next load change use in our strategy. Only 0.9122 kg extra coal is expensed during once control process.